Peripheral chemoreflex modulation of renal hemodynamics and renal tissue PO2 in chronic heart failure with reduced ejection fraction - Kious, Kiefer W.; Philipose, Andrew; Smith, Luke J.; Kemble, Jayson P.; Twohey, Stephanie C. E.; Savage, Kalie; Díaz, Hugo S.; Del Rio, Rodrigo; Marcus, Noah J. (Frontiers in Physiology, 2022)
Aberrant carotid body chemoreceptor (CBC) function contributes to increased sympathetic nerve activity (SNA) and reduced renal blood flow (RBF) in chronic heart failure (CHF). Intermittent asphyxia (IA) mimicking sleep apnea is associated with additional increases in SNA and may worsen reductions in RBF and renal PO2 (RPO2) in CHF. The combined effects of decreased RBF and RPO2 may contribute to biochemical changes precipitating renal injury. This study sought to determine the role of CBC activity on glomerular filtration rate (GFR), RBF and RPO2 in CHF, and to assess the additive effects of IA. Furthermore, we sought to identify changes in gene expression that might contribute to renal injury. We hypothesized that GFR, RBF, and RPO2 would be reduced in CHF, that decreases in RBF and RPO2 would be worsened by IA, and that these changes would be ameliorated by CBC ablation (CBD). Finally, we hypothesized that CHF would be associated with pro-oxidative pro-fibrotic changes in renal gene expression that would be ameliorated by CBD. CHF was induced in adult male Sprague Dawley rats using coronary artery ligation (CAL). Carotid body denervation was performed by cryogenic ablation. GFR was assessed in conscious animals at the beginning and end of the experimental period. At 8-weeks post-CAL, cardiac function was assessed via echocardiography, and GFR, baseline and IA RBF and RPO2 were measured. Renal gene expression was measured using qRT-PCR. GFR was lower in CHF compared to sham (p<0.05) but CBD had no salutary effect. RBF and RPO2 were decreased in CHF compared to sham (p<0.05), and this effect was attenuated by CBD (p<0.05). RBF and RPO2 were reduced to a greater extent in CHF vs sham during exposure to IA (p<0.05), and this effect was attenuated by CBD for RBF (p<0.05). Downregulation of antioxidant defense and fibrosis-suppressing genes was observed in CHF vs. sham however CBD had no salutary effect. These results suggest that aberrant CBC function in CHF has a clear modulatory effect on RBF during normoxia and during IA simulating central sleep apnea.